Lateral side impact crash simulation of restrained 3 year old child - Shasthri, Sevaguru; Venkatason, Kausalyah; Shah, Qasim Hussain; Idres, Moumen; Abdullah, Kassim Abdulrahman; Wong, Sha Voon (Trans Tech Publications Ltd., Switzerland, 2014)
Motor vehicle crashes have become the leading cause of death for children in many developed countries and the trend is on the rise in Malaysia. Child anatomy and physiology necessitates a separate restraints system to be implemented during vehicle travel. Although approximately twice as many crashes with a child fatality are frontal compared to lateral, it is shown that side impacts are nearly twice as likely to result in a child fatality as frontal impacts. Due to the complexity and the highly non-linear nature of vehicle crash affecting occupants, much work still remains to be looked into. This is especially so in the study of injury mechanisms towards efforts of improving CRS design as well as vehicle parameters that may offer more effective and robust injury mitigation. The study here presents a methodology which outlines the development and testing of a simulation model where a 3 year old child, restrained in a CRS within a vehicle, is subjected to lateral side impact by a bullet vehicle. A combined environment of both Finite Element as well as Multi-body is used for the model development. A HYBRID III dummy model is used to represent the child while an FE model is used for the CRS model. A hybrid modelling method is utilized for the belt harness system. The model and simulation conditions are set based on the global FMVSS standard. Head injury criterion and Neck injury criterion are primarily considered in the model assessment. Model development as well as validation steps are presented with discussion of the model’s salient features for greater insights in the study of injury mechanisms.